PROTOTYPE APLIKASI SISTEM REKAM MEDIS PASIEN BERBASIS WEB PADA KLINIK KARAWACI MEDIKA - Maimunah Maimunah; Muhaimin Hasanudin; Anggi Prabowo (Universitas Raharja, 2019)
The application of technology in the health field can facilitate all the work of in particular the registration and processing of data which require speed, accuracy and kevalidan data. The patient's medical record application prototype web-based aim to do the fulfillment of those needs at the clinic. During the process of running the clinic, Karawaci Medika outpatient process with the patient's medical record cards are kept by the clinic that shaped paper patient medical record card so that it is difficult to be found when the patient's medical record data required for the inspection of outpatient and outpatient registration on, patients are required to wait for quite a long time because it is still the manual registration process of the patient. From that problem-solving is obtained i.e. prototype applications can make admin in dealing with patient data, manage and facilitate the registration of patients in outpatient as well as see medical record anytime and anywhere. Make it easier for patients in outpatient diperlu because it does not carry an outpatient card so that patients as well as klink could be same same rototype helped by the existence of the patient's medical record application is web-based. This research is created by using the method of observation, interview methods, SWOT analyst and studies of the literature. Using UML as modeling designs